Portugal e a Inglaterra nos tempos modernos - Cardoso, António Barros (2003)
The first visit by John Methuen to Lisbon in May 1703 strengthened the Anglo-Portuguese friendship begun during medieval times with the Windsor Agreement. The entry of Portugal into the Great Alliance, next to England, the Netherlands, Germany and Austria, against Spain and Louis XIV's France represented an important political milestone. On 27th December of that same year, the signature of the treaty that has been perpetuated in our collective memory under the name of the English charge d'affaires in Portugal, provided Portugal with a renewed economic position at the side of its traditional ally and opened the way to economic interdependence between our country and England during Modern Times, established through treaties signed immediately after the reconquest of our independence in 1640.